Implementasi Hadis-hadis Tentang Tanggung Jawab Kepemimpinan: Studi Ma’anil Hadis - Muhammad Hamdi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the concept of leadership in Islam through a qualitative analysis of the hadiths of Bukhari and Muslim. It explores the deeper meaning of leadership as a trust that carries moral and spiritual responsibility. It does so using a desk research methodology. Key findings demonstrate that everyone is responsible for leadership, what happens with misguided leadership, and what happens with unjust leadership. The ma'anil hadith method facilitates a deeper understanding of key terms, enriches the interpretation of hadith, and demonstrates its relevance to the modern world. The study finds that the hadiths outline the principles of accountability, transparency, and justice, which remain crucial for ethical and responsible leadership today.